Предмет: Математика,
автор: Аноним
Решите уравнение:
(x-2)³+(x+2)³ = 2(x-3)(x²+3x+9).
Ответы
Автор ответа:
1
Ответ:
(х-2)^3+(х+2)^3=2(х-3)(х^2+3х+9)
x^3 - 6x^2 + 12x - 8 + x^3 + 6x^2 + 12x + 8 = 2(x^3 - 27)
2x^3 + 24x = 2x^3 - 54
24x = - 54 /: 24
x = - 9/4
Ответ: - 9/4
Аноним:
спасибо огромнейшее!!!♡♡♡♡
Похожие вопросы
Предмет: Другие предметы,
автор: cavahir10
Предмет: Английский язык,
автор: Милена15101
Предмет: Алгебра,
автор: yuliyaru12
Предмет: Алгебра,
автор: neznaika12332
Предмет: Русский язык,
автор: Angelbskaya1506